Inovasi Pembelajaran Kajian Drama Berbasis Pementasan Digital: Transformasi Pendidikan Bahasa dan Sastra Indonesia di Era Disrupsi - Een Nurhasanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to explore students' experiences, reflections, and perceptions of innovative learning in drama studies through digital performance. This qualitative descriptive research utilized a case study approach with 36 students enrolled in the Drama Studies course (2025/2026) within the Indonesian Language and Literature Education program at Universitas Singaperbangsa Karawang. Primary data consisted of students' written reflections and digital performance artifacts, supported by secondary data from literature on constructivism, dual coding/multisensory theory, and emotional intelligence, as well as curriculum documents. Data collection involved documentation, participatory observation, and semi-structured interviews. Data analysis employed thematic analysis through systematic steps including reading, coding, categorization, interpretation, and presentation. Data validity was ensured through source triangulation, member checking, and peer debriefing. The findings indicate that digital performance provides positive learning experiences, strengthens the integration of theory and practice, fosters problem-solving skills, and develops collaboration, empathy, and students' emotional intelligence. These results affirm that digital performance-based drama learning is a pedagogical innovation relevant to 21st-century competencies and can serve as a model for project-based curriculum development in literature education.